Novel eco-friendly PVA/Alginate biocomposites containing C.niveum extract: Development, characterization and optical properties - Pekdemir, Sibel Selcuk; Kuzu, Serpil Yalcin; Pekdemir, Mustafa Ersin; Sancar, Pelin Yilmaz; Koek, Mediha (Springer, 2024)
This study explores the development of eco-friendly biocomposite films incorporating Poly(vinyl alcohol) (PVA), Alginate, and Cyclotrichium niveum (C. niveum) extract. The research emphasizes the fabrication of PVA/Alginate blend biocomposites produced by solvent casting with varying concentrations of C. niveum, analyzing their physicochemical, biochemical, and optical characteristic features. These biocomposites exhibited enhanced properties making them suitable to for applications such as packaging, and agricultural films. Significant outcomes of the research include the biocomposites improved thermal stability and semiconductor properties, evidenced by the decrease in band gap energy as the concentration of C. niveum increases. This work underscores the crucial role of integrating natural and synthetic polymers to address environmental challenges posed by traditional plastics, steering the field toward sustainable material solutions.
Keywords: Poly (vinyl alcohol); Alginate; Cyclotrichium niveum; Composite film; Optical absorption